Pengaruh Kompetensi Sosial, Iklim Kerja dan Motivasi Berprestasi Terhadap Kinerja Guru di SLB Se-Kota Yogyakarta - Kusnadi, Kasmiyati (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study was to find out how much influence social competence has on teacher performance, work climate on teacher performance, motivation on teacher performance and the influence of work climate competence, and motivation on teacher performance in special schools throughout the city of Yogyakarta. The research method used is quantitative. The sampling technique is done by population sampling, data collection uses research instruments, and data analysis uses quantitative or statistical methods. This research is a research with a descriptive approach with the aim to be able to describe the research results well. The results showed that there was a positive and significant effect of social competence, work climate and achievement motivation on the performance of SLB teachers in the city of Yogyakarta by 59.7%. Teacher performance is highly dependent on social competence, work climate and achievement motivation. If the social competence, work climate and achievement motivation are higher, then the disturbed teacher's performance becomes optimal. However, if social competence, work climate, and motivation are lacking, the teacher's performance is likely to be less than optimal.